Construction and effectiveness of a pharmacist-involved diabetes management model between tertiary hospitals and community under the hierarchical medical system - Gao, Nan; Lan, Linyan; Jia, Zizhen; Li, Huaying; Xie, Xiangxiang; Xie, Han; Ji, Cheng (Frontiers in Clinical Diabetes and Healthcare, 2025)
ObjectiveThis study constructed a tertiary hospital-community health service center diabetes linkage management model with the participation of clinical pharmacists, assessed the changes in clinical indicators and medication treatment of patients with type 2 diabetes before and after the implementation of the model, and evaluated the model, with a view to providing a model reference in the participation of clinical pharmacists in the management of type 2 diabetes and other chronic diseases. Given the current situation that diabetes management at the community level in China is still unsatisfactory, with an HbA1c control rate of less than 10% compared to about 50% in tertiary hospitals, there is an urgent need to explore innovative, pharmacist-involved models to bridge this gap.MethodsUsing the principle of randomization, patients who met the enrollment criteria were divided into the experimental group and the control group. A total of 210 patients were enrolled from three community health service centers in Nanjing in collaboration with Drum Tower Hospital, and were followed up for 12 months. Clinical indicators and medication adherence were used as evaluation endpoints to compare the differences in management effects between the two groups. This study was registered with the Chinese Clinical Trial Registry (ChiCTR2300074444).ResultsUnder the diabetes linkage management model, patients in the intervention group showed improvement in blood glucose, glycated hemoglobin and other indicators compared with the control group; the medication adherence score of patients in the intervention group was significantly higher than that of the control group.ConclusionThe clinical efficacy and medication level of diabetic patients were significantly improved after management by this management model, which provides a reference for clinical pharmacists to carry out pharmacy services in the context of hierarchical diagnosis and treatment. This model may contribute to narrowing the quality gap between tertiary hospitals and community health service centers in diabetes care.